The effectiveness of the interest rate channel in the conduct of monetary policy, and the relationship between long-term and short-term interest rates in the Canadian context - Wen, Zhu (Université d'Ottawa | University of Ottawa, 2004)
The aim of this paper is to investigate whether the Bank of Canada has been successful in conducting monetary policy through one of the most important channels of transmission mechanism - the interest rate transmission channel- specially after the mid-199